Analysis of the Seasonal Variation in Turbidity Index in Sudan and Fresh Water Swamp Vegetation Zones, Nigeria - Muhammad, S. U.; Solomon, W. C.; Yahaya, D. B.; Enaburekhan, J. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This study evaluates the seasonal turbidity index of two vegetation zones in Nigerian which are Sudan and Fresh water swamp. Thirty years (1981 – 2010) meteorological data of temperature, relative humidity and solar radiation were obtained from the archives of the Nigerian Meteorological agency (NIMET). Annual and monthly analysis of the turbidity coefficients were mainly based on the Linke and Angstrom methods, due to absence of radiosonde data. The results show that the monthly mean values of the clear-sky global radiation lies between 19.34 MJ/m2day to 24.44 MJ/m2day (for Sudan vegetation) and 15.54 MJ/m2day to 20.28 MJ/m2day (Fresh water swamp). Meanwhile, the monthly percentages of clearness index above 0.6 were estimated as 75% and 33.3, and for the water vapour content exceeding 3 cm to be 58.3% and 100%, for the Sudan and Fresh swamp vegetation, respectively. These values contribute significantly to the reduction of direct radiant energy. The results obtained for the seasonal index for Linke and Angstrom coefficients show that for the wet season, the index exceeded the dry value by 25.99% and 23.66% for Sudan and Fresh swamp vegetation, respectively. By implication, the Fresh water Swamp is laden with more aerosols than Sudan zone. Additionally, the R2 obtained for the relationship between Angstrom and Linke is 0.999 for both locations. Hence, the study provides an insight into the contribution of aerosol in the attenuation of solar radiation over the atmosphere for these locations.